Analysis of Review of the Principles of Law and Justice Principles in Indonesia (Study on the Constitutional Court’s Decision Number 66 / Pu-XIII / 2015) (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aims to find out how the basic idea of ​​the existence of a Reviewing Institution in criminal proceedings in realizing legal certainty and justice; Implications of the decision of the Constitutional Court Number 66/PU-XIII / 2015 and the formulation policy on future review of the Criminal Procedure Code. This research is normative legal research. The approach used is the law approach; conceptual approach and comparative approach. The results of this study are: In accordance with the nature of the final and binding decision of the constitutional court, the Constitutional Court Decision Number 66 / PU-XIII / 2015 refers to the fundamental principle that justice is the highest legal objective. Citizens’ rights as guaranteed by the constitution must not be restricted because they are guaranteed by the constitution. Based on a comparative formulation study in several countries such as in the Chinese Criminal Procedure Code and the Dutch Criminal Procedure Code, the regulatory norms regarding the number of times the Submission of Judicial Review may be submitted are not formulated but the KUHAP of the two countries further regulates in detail the mechanisms and procedures for the Judicial Review. Then the policy formulation of norms for reviewing the KUHAP in the future in addition to referring to the comparison but also must be constitutional in accordance with the decision of the Constitutional Court Number 66 / PUU-XIII / 2015.